(untitled) (Training and Practice : Journal of Educational Sciences, 2022)
The roots of financial literacy ideally go back to childhood, but experience from higher education suggests that there is still work to be done in training librarians and information professionals. This paper examines the current curricular practices of domestic library and information science education programmes aimed at developing financial literacy, with a particular focus on the curricula of the Institute of Library and Information Science of the Faculty of Humanities of Eötvös Loránd University, covering the full spectrum of education (bachelor’s, master’s, teacher and doctoral training programmes), both full-time and part- time. The expected outcome of the university training is not only to raise the level of financial literacy through library tools, but also to improve the economic and managerial skills of librarians and, indirectly, their social recognition.